Powiązania wskaźnika placów 2D:4D z cechami budowy ciała i sprawnością motoryczną u młodych piłkarzy = The relationship digit ratio 2D:4D with body build features and motoric performance in young footballers - Mońka, Magdalena; Pietraszewska, Jadwiga (Journal of Education, Health and Sport, 2017)
Mońka Magdalena, Pietraszewska Jadwiga. Powiązania wskaźnika placów 2D:4D z cechami budowy ciała i sprawnością motoryczną u młodych piłkarzy = The relationship digit ratio 2D:4D with body build features and motoric performance in young footballers. Journal of Education, Health and Sport. 2016;6(11):73-86. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163952 http://ojs.ukw.edu.pl/index.php/johs/article/view/3964 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 31.10.2016. Powiązania wskaźnika placów 2D:4D z cechami budowy ciała i sprawnością motoryczną u młodych piłkarzy The relationship digit ratio 2D:4D with body build features and motoric performance in young footballers Magdalena Mońka1, Jadwiga Pietraszewska2 1 Doktorantka na Wydziale Wychowania Fizycznego Akademii Wychowania Fizycznego we Wrocławiu 2 Zakład Antropologii Fizycznej Akademii Wychowania Fizycznego we Wrocławiu Mgr Magdalena Mońka1, dr hab. Jadwiga Pietraszewska, prof. nadzw.2 Słowa kluczowe: wskaźnik 2D:4D, piłkarze nożni, budowa ciała, sprawność motoryczna Key words: index 2D:4D, football players, body build, motoric fitness Streszczenie Proporcja długości palców 2D:4D wykazuje dymorfizm płciowy. Mężczyźni mają niższą wartość tego wskaźnika w stosunku do kobiet. Jest to wynik działania hormonów płciowych -androgenów. Badania wskazują, że wysoki poziom testosteronu, przejawiający się w niższej wartości ilorazu palców, determinuje lepszą wytrzymałość, zręczność, większą siłę oraz skłonność do agresji i podjęcia walki. Cechy te są istotne w odnoszeniu sukcesów sportowych. W badaniach poszukiwano zależności formuły palców z budową ciała, sprawnością motoryczną i osiąganymi wynikami w sporcie. Publikowane wyniki nie są jednak jednoznaczne w odniesieniu do cech sprawnościowych. Cel Celem niniejszej pracy było sprawdzenie, czy w populacji polskiej, wśród młodych piłkarzy nożnych, wartość wskaźnika 2D:4D wykazuje powiązania z cechami budowy morfologicznej i poziomem sprawności motorycznej. Materiał i metody Materiał badawczy stanowią wyniki pomiarów podstawowych cech antropometrycznych oraz sprawności motorycznej piłkarzy nożnych (n=38) Klubu Sportowego Polkowice. Wiek badanych mieści się w przedziale 16-18 lat. Ich staż zawodniczy wynosi co najmniej 6 lat. U wszystkich badanych osób zmierzono także długość drugiego i czwartego palca, na podstawie tych wartości wyliczono wskaźnik 2D:4D dla ręki prawej i lewej. Do oceny sprawności motorycznej badanych wykorzystano następujące próby motoryczne: skłon w przód w siadzie, skok w dal z miejsca i siady z leżenia. Próby zostały przeprowadzone zgodnie z procedurą testu Eurofit (1993). Dodatkowo wykonano pomiar siły ścisku ręki przy pomocy dynamometru. Wyniki Wskaźnik 2D:4D przyjmuje u badanych piłkarzy typowe dla mężczyzn wartości. Stwierdzono jednak słabe związki formuły palców z cechami budowy somatycznej oraz z niektórymi komponentami sprawności motorycznej. Summary The ratio of the finger’s length 2D: 4D shows sexual dimorphism. Males have a lower digit ratio in comparison to women. This is the result of the sex hormones –androgens. Researches indicate that high level of testosterone determines better strength, dexterity, greater force and tendency to aggression and to fight. These features are important to succeed sports. The studies have verified relationship digit ratio 2D:4D with body build and motor performance as well as results in sport. The published results are not conclusive with reference to the characteristics of fitness. Aim of study The aim of the study was examine if the value index 2D: 4D among Polish, young soccer players correlates with morphological features and level of motoric performance. Material and methods The researches are conducted in group of 38 soccer players from Sport Club Polkowice. The age of examined was 16-18 years old. The professional training was at least 6 years. There was measured digit ratio, basic anthropological features and motoric efficiency. There was used three motoric tests: sit-ups, standing long jump and flexibility. Conclusion Digit ratio indicates low relationship with the characteristics of the somatic construction and some components of the motoric performance.